Consolidating an experimental pedagogy: Exploring ecologies of film education within France's Cinéma Cent Ans De Jeunesse and Scotland's Understanding Cinema project(s) between 2013 and 2019. Issue 2 (26th November 2020) - Chambers, Jamie
Abstract : page_138 other The Cinémathèque Française's long-running Cinéma Cent Ans De Jeunesse (CCAJ) has become one of the most influential film education projects in the world today. This article reflects critically and in detail upon five years of the delivery of the project in Scotland, considering the changing pedagogical shapes of the project's 'curriculum' alongside changing ecological factors (such as class size and age and lesson time) in considering how a small nation such as Scotland might best employ CCAJ as a means of addressing foundational film education.